KEANEKARAGAMAN JENIS IKAN DI SUNGAI BATANG BUNGO DUSUN TEBAT KECAMATAN MUKO-MUKO BATHIN VII KABUPATEN BUNGO PROVINSI JAMBI - Ahmad Fajri; Rini Hertati; Syafrialdi Syafrialdi (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
The general waters of mainland Indonesia include swamps, rivers and likes, which have a high diversity of fish species. This research was carried out in Tebat Hamlet, Muko-Muko Bathin VII District, Bungo Regency, Jambi Province which was divided into three research ststationsrom August to November 2021. This study aimed to find out what fish were caught and he level of fish diversity in the Batang Bungo River, Tebat Hamlet, Muko-Muko Bathin VII District, Bungo Regency, Jambi Province. The method used in this research is Purposive Sampling to determine the research area, while for sampling with fishing gear, using the Random Sampling Method. From the research result, the diversity index analysis for station one is 1.57, station two is 1.54, and station three is 1.97, the most caught fish at all stations were from the Family Cyprinidae with Malih (Labiobarbus lineatus), Masai (Mystacoleusus marginatus), and Semuruk (Ostheochilus vittatus) species.